Body composition and SEMG amplitude of the spine rectifier in children with scoliotic lesions - Jacek Wilczyński; Przemysław Karolak; Sylwia Janecka (Kazimierz Wielki University, 2018)
The aim of the study was to analyze the relationship between body composition and the amplitude of SEMG rectifier spine in children with scoliotic changes. The spine was investigated using optoelectronic Diers formetric III 4D. Body composition was determined using a Tanita Body Composition Analyzer MC 780M. Analysis of the amplitude SEMG rectifier spine was performed using a 12-channel camera Noraxon TeleMyo DTS. The biggest differences in the absolute values of the studied variables related to body composition BMR (kJ). The most important and statistically significant predictors mock for the variable composition of the body spine and amplitude rectifier tested in different positions in the group of scoliosis proved standing position lumbar left (p = 0.01), standing position lumbar right (p = 0.01) and lying front right side of the thoracic (p = 0, 02). The variance explained by the independent variables in the model adopted is 35% of the total variation (R^2 = 0.35), indicating a small adjustment for the data, but the expected level of statistical significance (p = 0.01) has been fulfilled, and to give the corresponding the value of a statistical test F = 3.49. The group scoliotic bases most important and statistically significant predictor model was the torso up right thoracic (p = 0.0001), lower limbs up the right side of the lumbar (p = 0.044), trunk up the right side of the lumbar (p = 0.016) and the top of the torso thoracic left (p = 0.006). The model was explained only in 39% (R^2 = 0.39), which is low, but the target level of statistical significance (p = 0.001) was also satisfied. and give the corresponding value of the statistical test F = 4.89. In children with scoliotic changes SEMG amplitude measurement helps identify the muscles need strengthening or relaxation, as well as the selection of appropriate corrective exercises.